Tactile perception of spatial stimuli on the lip surface by young and older adults - Wohlert, A B (Journal of speech and hearing research, 1996)
Although older adults are subject to both subtle changes and major disorders of the oral sensorimotor system, relatively little is known about oral sensory function in old age. Accurate assessment of oral tactile perception is needed to document disability, aid prognosis, and plan treatment for older adults with disorders affecting speech or feeding. However, normative information currently available for older adults is mainly based on two-point discrimination, a problematic measure of tactile spatial resolution. Grating orientation discrimination, a technique developed to provide a clear and reliable measure of spatial resolution, was used to test sensitivity of the upper and lower lip vermillion, on right and left sides, in a sample of 40 young adults and 40 adults age 66-85. Results indicated that spatial acuity at the lip vermilion declines significantly in old age and that women tend to have better acuity than men. No significant differences were found in acuity between the upper and lower lips or between right and left sides for either age group. Peripheral changes in receptor density and lip tissue composition are suggested as likely causes for the age-related decline.